Randomized, Comparative Assessment of the Functional and Radiological Outcome in Management of Type IIIB Tibial Fractures Using Two Different Methods (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2022)
Aim: to determine the comparison of Radiological & Functional outcome & complications of the open tibial type IIIB fractures treated with primary Ilizarov external ﬁxator and AO external ﬁxatorsMethodology: This is a Randomized, comparative study conducted on Patients with open tibial class IIIB fractures admitted in Vardhman Institute of Medical Science, Pawapuri, Nalanda, Bihar, India. A number of 40 patients satisfying the inclusion criteria have been treated by Ilizarov technique and 40 patients treated by AO external ﬁxator in the previous 2 years.The follow up would be for one year. Initially for every 3 weeks in ﬁrst 6 weeks for wound care, every 6 weeks for one year and assessed by Radiological evidence of union of fracture and Functional assessment by Patient’s Functional and Bone results are assessed based on ASAMI (Association for the study and application of the methods of Ilizarov) criterion and complications. The data was recorded and analyzed.Results: Most of the fractures were observed in 31-40 age groups. Mean Age in AO group is 47.4 + 12.5years and Ilizarov group is 41.6 + 14.7 years with male preponderance in the Gender Distribution of both Groups, being 87.5 % and 85 % in Group A and B, respectively.ASAMI bone results & functional results were Excellent (25%), Good (67.5%) & Poor (7.5%) in AO group, whereas in Ilizarov group Excellent (62.5%), Good (32.5%) & Poor (5%). Ilizarov has good Functional scoring when compare to AO group most common complications encountered were Pin Tract Infections, pain, stiffness, limp. In AO group pin tract infections were seen in 21, pain in 13, stiffness 10, limb length discrepancy in 4, Non-union in 3 and malunion in 1 patient. In Ilizarov group pin tract infections were seen in 15, pain in 9, stiffness in 7, limb length discrepancy in 3, Non-union in 2 & malunion in 2 cases.Conclusion: It can be concluded that the efficacies of treatment with Ilizarov was higher than AO external fixator in treatment of tibia open type IIIB fractures.